Radio Frequency Identification (RFID) Technology Devices in Library Services: Improving Education Services - Komalasari, Yeti; Abdullah, Anton; Yiharodiyah, Lisa; Sutiyo, Sutiyo; Parjan, Parjan; Amanda, Monica (Graduate Program Magister Manajemen Pendidikan, 2023)
As educational institutions, libraries must innovate to provide higher-quality services. Libraries are no longer managed in the traditional way and are beginning to use information technology known as library automation. RFID technology devices are used to carry out the automation circulation service. This study was done to measure user satisfaction with the usage of RFID technology in library services as well as the efficiency of library services in assisting existing educational services. This kind of quantitative research employs observational methods, a descriptive study design, and the distribution of research questionnaires to participants. The usage effectiveness value for the research indicated that the combination of the cadet identification card and the library membership card into a single card was deemed to be effective and efficient at 96%, which was a considerable increase. The adoption of RFID technology has increased circulation service standards, is more flexible than traditional modes, and promotes digital-based libraries, with a level of customer satisfaction with the use of RFID technology devices in circulation services of 97.2%. The high value of effectiveness and user happiness with the application of RFID technology in library services are indicators of success.